ANALISIS PERAN GURU PAK DALAM MENGATASI PERILAKU BURUK TERHADAP SISWA SDN 101 MAKALE 4 DARI PERSPEKTIF PENDIDIKAN KONSIENTISASI - Soviana Sanda Lembang; Eva Palangiran; Priskila Priskila; Merlinda Rara’ (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
The purpose of this research is to know the role of Christian religious education in overcoming students' bad behavior. Bad behavior usually arises from actions that violate rules or regulations. Bad behavior towards students can usually harm the people around them, such as damaging the learning atmosphere and being disrespectful to the teacher. So the research method used is a qualitative research method where the author analyzes by collecting data, namely observation interviews with data management techniques through data reduction, data display, and drawing conclusions. From the results of the study that the form of bad behavior of SDN 101 Makale 4 students, namely fighting, is one of the unpleasant actions because it disturbs friends who are studying in class. Mocking the teacher is an act. Arguing the teacher is a bad action because it is not polite to the teacher. in SDN 101 Makale 4 most students exhibit bad behavior. Because teachers at SDN 101 Makale 4 when students have problems the teacher only reprimands them without being firm with students.